Bipedicled SIEA Flap with Deep Inferior Epigastric Artery and Vein Grafts for Breast Reconstruction - Ryota Nakamura, MD; Koichi Tomita, MD; Nanaho Omura, MD; Eriko Nishimura, MD; Kyuto Higashimoto, MD; Tateki Kubo, MD; Hisashi Hikasa, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. A superficial inferior epigastric artery (SIEA) flap can be an alternative to a deep inferior epigastric artery perforator (DIEAP) flap in cases where SIEAs are relatively well developed. Although an SIEA flap is less invasive than a DIEAP flap, the pedicles of the former are anatomically shorter, making it more difficult to choose recipient vessels when bilateral SIEAs are necessary. A 45-year-old female diagnosed with cancer of the left breast underwent mastectomy (specimen weight: 750 g) and immediate two-stage breast reconstruction using a free abdominal flap with bilateral pedicles was planned. Preoperative computed tomographic angiography showed that the bilateral DIEAPs in the flap were less than one millimeter in diameter, whereas the bilateral SIEAs were well developed enough for us to opt for a double-pedicled stacked SIEA flap. After the double-pedicled SIEA flap was elevated, folded, and temporarily placed in the subcutaneous pocket, the pedicle length on one side was found to be insufficient. Therefore, portions of the right composite deep inferior epigastric artery (DIEA) and vein (DIEV) grafts (roughly 7 cm) were collected from a short fasciotomy and anastomosed to the peripheral ends of the right SIEA and SIEV, respectively. Following this, the left SIEA and SIEV were antegradely anastomosed to the internal mammary artery and vein (IMA/IMV), while the DIEA/DIEV grafts were retrogradely anastomosed to the IMA/IMV, respectively. We recommend the proactive use of this method, as pedicle extension using the DIEA/DIEV grafts enables a higher degree of freedom in unilateral breast reconstruction using bilateral SIEA flaps.